On speech enhancement algorithms based on mmse estimation - SCALART, Pascal; FILHO, Jozue VIEIRA [UNESP]; CHIQUITO, José GERALDO (My University, 2015)
This paper addresses the problem of single microphone frequency domain MMSE noise reduction technique for speech enhancement in noisy environments. We first analysed asymptotic performance of the MMSE estimate and compared these results with the Wiener filter. Practical implementation of the MMSE filter is then presented. Comparisons between optimal and practical behaviour of the MMSE filter demonstrate that an effective improvement in the noise reduction process can be gained if greater attention is given to the these estimators.